2020
DOI: 10.1111/hsc.13201
|View full text |Cite
|
Sign up to set email alerts
|

Dog‐assisted interventions in care homes: A qualitative exploration of the nature, meaning and impact of interactions for older people

Abstract: Dog-assisted interventions (DAI) have been shown to have a wide-range of potential benefits for older adults living in care homes. Yet, there is a lack of published qualitative research which explores the experiences of care home residents, staff and dog-owner volunteers involved in DAI to fully understand its meaning, impact and value. This study aimed to explore the impact of a DAI on the social and emotional wellbeing of older residents living in care homes. The research employed a qualitative study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
“…All the quantitative studies were at either high or moderate risk of bias (Table 1). Only four of the qualitative and mixed methods studies scored ‘high’ for reliability (Damianakis & Wagner, 2007; Gundersen & Johannessen, 2018; Hunter et al., 2018; Jain et al., 2020). The four questionnaire studies fulfilled six ( n = 1) and seven ( n = 3) of the twelve categories on which they were judged.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations